Development of History-Based Animated Video Learning Media on Archimedes' Law Material - Agustam, Nur Fahra; Syukur, Muh Syarif S Abd; Wahyono, Unggul; Ratnaningtyas, Delthawati Isti (Journal of Innovative Physics Education Research, 2025)
This study aims to develop learning media in the form of history-based animated videos on Archimedes' principle and to test its feasibility and effectiveness in supporting the physics learning process. The research method used is the 4D development model, which includes the stages of define, design, develop, and disseminate. The subjects in this study involved 37 students from Labschool Untad Palu High School. The research instruments included validation sheets for media experts, subject matter experts, and practitioner experts, as well as student response questionnaires. The validation results showed that the developed learning media received a rating of Very Good from all experts, indicating that the media was suitable for use in learning. Trials with students on a limited and large scale also showed positive responses with a rating of Good. Based on these results, it can be concluded that the history-based animated video media on Archimedes' Principle material is deemed feasible and can be used as a supporting tool in physics learning activities.